Increased triglyceride-glucose index is associated with adverse functional outcome for patients with aneurysmal subarachnoid hemorrhage after surgical clipping and endovascular coiling: insights from a large cohort study - Tang, Xielin; Zhu, Bingcheng; Liu, Minghao; Lin, Fa; Li, Runting; Song, Wenxiong; Xue, Jionghao; Zhou, Liangxue; Chen, Xiaolin (Frontiers in Neurology, 2025)
BackgroundThe triglyceride-glucose index (TyG-i) isrecognized as a simple, cost-effective, and valuable surrogate for insulin resistance, and it has been identified to be associated with the prognosis of cardiovascular diseases. However, limited research has been conducted to explore the relationship between TyG-i and clinical outcome of aneurysmal subarachnoid hemorrhage (aSAH). This study aims to elucidate the association between preoperative TyG-i level and the prognosis of aSAH.MethodsA total of 467 patients with aSAH admitted to Beijing Tiantan Hospital from January 2015 to September 2022 for inclusion in this study. Unfavorable clinical outcome was defined as modified Rankin Scale (mRS) < 3 at 90 days after discharge. TyG-i was calculated using measurements of triglyceride and fasting blood glucose. Additionally, TyG-body mass index (TyG-BMI), a TyG-derived parameter calculated by TyG-i, height, and weight, was also collected. Multivariate logistic regression analysis was performed to explore association between clinical outcome and TyG-i level, as well as its derivative index.ResultsAfter multivariate adjustment, the increased TyG-i level was associated with high risk of unfavorable clinical outcome (Odds ratio = 3.474, p = 0.002). Multivariable-adjusted spline regression model showed a linear relationship between TyG-i and aSAH prognosis (p for nonlinear = 0.202). Moreover, adding TyG-i to conventional risk factors significantly improved the risk prediction of poor prognosis (net reclassification index: 40.17%, p < 0.001; integrated discrimination index: 3.24%, p = 0.005). Multivariate logistic regression analysis demonstrated that there was no significant association between TyG-BMI and clinical outcome of aSAH.ConclusionHigh preoperative TyG-i levels were associated with increased risks of unfavorable clinical outcome, suggesting that TyG-i may be a valuable prognostic marker for patients with aSAH.Clinical trial registrationhttps://clinicaltrials.gov/ct2/show/NCT04785976, identifier NCT04785976.